2021
DOI: 10.1101/2021.05.12.443914
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromosome length and gene density contribute to micronuclear membrane stability

Abstract: Micronuclei are derived from missegregated chromosomes and frequently lose membrane integrity, leading to DNA damage, innate immune activation, and metastatic signaling. Here we demonstrate that two characteristics of the trapped chromosome, length and gene density, are key contributors to micronuclei membrane stability in human cells. Chromosome length is proportional to micronuclei size, and gene density has an additive effect with micronucleus size on membrane stability. We demonstrate that these results ar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…We found that the micronuclei that result from ensheathed chromosomes had disrupted envelopes 8 h post-release from CENP-E inhibition. Rupture of micronuclei has been shown to lead to DNA damage, and activation of innate immune and cell invasion pathways (Ly et al, 2017;Hatch et al, 2013;Mammel et al, 2021;Bakhoum et al, 2018). The presence of ER in the micronuclear space of disrupted micronuclei indicates that ensheathing may increase the likelihood of rupture, we speculate that this may occur by endomembranes physically interfering with envelope reformation at the micronucleus.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We found that the micronuclei that result from ensheathed chromosomes had disrupted envelopes 8 h post-release from CENP-E inhibition. Rupture of micronuclei has been shown to lead to DNA damage, and activation of innate immune and cell invasion pathways (Ly et al, 2017;Hatch et al, 2013;Mammel et al, 2021;Bakhoum et al, 2018). The presence of ER in the micronuclear space of disrupted micronuclei indicates that ensheathing may increase the likelihood of rupture, we speculate that this may occur by endomembranes physically interfering with envelope reformation at the micronucleus.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, the levels of either mCherry-BAF or LBR-mCherry were correlated with GFP-Sec61β. To confirm that these micronuclei had disrupted nuclear envelopes, we stained for H3K27Ac, a modification to Histone H3 that is removed by exposure to the cytoplasm (Mammel et al, 2021). Intact micronuclei had similar H3K27Ac signals to the corresponding main nucleus, whereas in micronuclei that were disrupted, the signal was lost (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, chromosomes trapped in micronuclei are prone to incomplete replication, DNA breaks, and chromosomal shattering leading to complex rearrangements (i.e., chromothripsis) (Crasta et al, 2012;Hatch et al, 2013;Zhang et al, 2015;Liu et al, 2018;Tang et al, 2022). There is evidence micronucleus instability can cause punctuated bursts of numerical and structural chromosomal alterations within a few cell divisions and promote inflammation, epithelial-tomesenchymal transition, and metastasis (Mackenzie et al, 2017;Bakhoum et al, 2018;Umbreit et al, 2020), but we are still learning about the cellular events leading to micronuclei rupture in normal and cancer cells (Sepaniac et al, 2021;Agustinus et al, 2022;Mammel et al, 2022;Papathanasiou et al, 2022). Chromothripsis is more frequent in WGD+ than WGD− cancers (Notta et al, 2016;Cortés-Ciriano et al, 2020), likely reflecting an increase in both the rates and tolerance of genomic alterations in tetraploid cells.…”
Section: Centrosome and Chromosome Partitioning During The Evolution ...mentioning
confidence: 99%